Natural Antibodies as Rheostats for Susceptibility to Chronic Diseases in the Aged - Rothstein, Thomas L. (Frontiers in Immunology, 2016)
Natural antibodies are spontaneously produced in the absence of infection or immunization, and are both anti-microbial and autoreactive. Autoreactive natural antibodies can bind noxious molecules, such as those involved in clinical situations of atherosclerosis (oxLDL), malignancy (NGcGM3) and neurodegeneration (amyloid, tau), and can affect the fate of their targets or the cells bearing them to maintain homeostasis. Clinically relevant natural antibodies have been shown to decline with advancing age in those few situations where measurements have been made. Consistent with this, human B-1 cells that are thought to be responsible for generating natural antibodies also decline with advancing age. These findings together suggest that an age-related decline in amount or efficacy of homeostatic natural antibodies is associated with relative loss of protection against molecules involved in several diseases whose incidence rises in the older age population, and that those individuals experiencing greatest loss are at greatest risk. In this view, natural antibodies act as rheostats for susceptibility to several age-related diseases. These considerations suggest that administration of natural antibodies, or of factors that maintain B-1 cells and/or enhance production of natural antibodies by B-1 cells, may serve to counteract the onset or progression of age-related chronic illness.